The Effectiveness Of Patchouli Leaf Decoction (Pogostemon cablin Benth) as a Bioinsecticide Against Aedes sp - Wenty, Darmayanita; Hardiansyah, Ikdal; Sultanul Aulya, Muhammad; Idris, Sri Aprilianti; Firdayanti; Susanti, Susanti (HEALTH SCIENCE & BIOMEDICAL JOURNAL, 2025)
Background: Aedes sp. is a primary vector responsible for transmitting several diseases such as dengue hemorrhagic fever, filariasis, chikungunya, leptospirosis, and bubonic plague. The expansion of its population from urban to rural areas necessitates new control measures. Patchouli leaves (Pogostemon cablin Benth) contain bioactive compounds such as flavonoids, tannins, and phenolic hydroquinone with potential mosquito-killing properties. Objective: To determine the effectiveness of boiled water extract of patchouli (Pogostemon cablin Benth) leaves against the mortality of Aedes sp. mosquitoes. Methods: An experimental design was used with three treatment groups receiving patchouli leaf extract concentrations of 80%, 90%, and 100%, along with a negative control (aquadest) and a positive control. Each treatment involved 25 mosquitoes with three replications. Observations were made over a 24 hour period (1440 minutes). Data were analyzed using a one-way ANOVA test. Results: The average mosquito mortality was 6.6 mosquitoes (27%) at 80% concentration, 11.6 mosquitoes (48%) at 90% concentration, and 16 mosquitoes (64%) at 100% concentration. Conclusion: The boiled water extract of patchouli leaves (Pogostemon cablin Benth) demonstrated effectiveness in increasing Aedes sp. mortality, with higher concentrations showing greater mosquito-killing activity.